2021
DOI: 10.1097/crd.0000000000000393
|View full text |Cite
|
Sign up to set email alerts
|

Role of MicroRNA in Heart Transplant

Abstract: The need for noninvasive biomarkers for diagnostic, prognostic, and therapeutic purposes is increasingly being recognized in the field of heart transplantation. MicroRNAs are a class of novel biomarkers that control gene expression and influence cellular functions, including differentiation, proliferation, and functional regulation of the immune system. They can be detected in the serum, plasma, and urine and may serve as early noninvasive biomarkers for various disease processes. Despite significant advances … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…MiRNAs are single stranded RNAs molecules about 22 nucleotides in length that can regulate gene expression at the post-transcriptional level and play a critical role in cardiac fibrosis, mainly including left ventricular fibrosis, right ventricular fibrosis and atrial fibrosis (Table 1 , Ref. [ 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 ]).…”
Section: Mirnas In Cardiac Fibrosismentioning
confidence: 99%
See 1 more Smart Citation
“…MiRNAs are single stranded RNAs molecules about 22 nucleotides in length that can regulate gene expression at the post-transcriptional level and play a critical role in cardiac fibrosis, mainly including left ventricular fibrosis, right ventricular fibrosis and atrial fibrosis (Table 1 , Ref. [ 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 ]).…”
Section: Mirnas In Cardiac Fibrosismentioning
confidence: 99%
“…In addition, many ncRNAs can be used as noninvasive detection indicators, such as for the assessment of myocardial injury after HT. MiR-133b has been found to be an important marker of myocardial injury and to be associated with hemodynamic changes evident early after transplantation [ 34 ]. Circ-FSCN1 silencing produced tolerogenic dendritic cells, which prevented alloimmune rejection in HT, prolonged patient survival and reduced myocardial fibrosis [ 71 ].…”
Section: Ncrnas and Other Factors Associated With Cardiac Fibrosismentioning
confidence: 99%
“…miRNAs are small, non‐coded, single‐stranded RNA sequences that regulate gene expression at a post‐transcriptional level. They circulate in stable forms in the blood and appear to play a role in endothelial homeostasis, making them a desirable biomarker for CAV 77‐79 . A cross‐sectional study, published in 2015, looked at endothelium enriched miRNAs and found they had the ability to discriminate between those with and without CAV and that certain miRNAs had greater diagnostic abilities than others 78 .…”
Section: Research and Future Directionsmentioning
confidence: 99%
“…biomarker for CAV. [77][78][79] A cross-sectional study, published in 2015, looked at endothelium enriched miRNAs and found they had the ability to discriminate between those with and without CAV and that certain miRNAs had greater diagnostic abilities than others. 78 Further studies continued to demonstrate specific miRNAs both in the serum and on endomyocardial biopsy as potential biomarkers for CAV.…”
Section: Biomarkersmentioning
confidence: 99%
“…Aside from advances in imaging, there has been a concurrent search for biomarkers associated with CAV for early detection and as potential treatment targets. These include osteopontin, a pro-inflammatory cytokine that correlates with severe CAV [39]; endothelin-1, a vasoconstrictor peptide associated with accelerated CAV development [40]; and various microRNAs [41][42][43], among others [44][45][46][47][48]. These markers still require prospective validation to assess their utility in CAV detection, as well as continued evaluation as possible treatment targets.…”
Section: Cardiac Allograft Vasculopathy Detectionmentioning
confidence: 99%